Vulnerability to freeze stress of seedlings of Quercus ilex L.: an ecological interpretation - Nardini, Andrea; Ghirardelli, Lia; Salleo, Sebastiano (Ann. For. Sci., 1998)
The vulnerability to freeze stress of seedlings of Quercus ilex L. was studied with the aim of defining the limits of the potential distribution area of this species in its northernmost habitat. In December 1996 seedlings were freeze stressed up to -8 °C for 3 d. Frost caused extensive functional damage to seedlings in terms of: a) leaf water status; b) root (Kr) and stem (Ks) hydraulic conductance; c) tissue disorder in the root (only nine seedlings out of 50 survived). In comparison with unstressed seedlings, Kr and Ks of freeze-stressed seedlings were reduced by 90 %. Root anatomy of freeze-stressed seedlings revealed that: a) cortex cells were dehydrated and had become separated from one another; b) the endodermis was oversuberized, thus isolating the stele from the cortex. Our conclusion was that Q. ilex is extremely vulnerable to freeze stress so that the distribution area of the species is restricted to zones with no frost events
Keywords: freeze stress; Quercus ilex L.; root and stem hydraulic conductance; water relations

Water relations of six sclerophylls growing near Trieste (Northeastern Italy): has sclerophylly a univocal functional significance? - Nardini, Andrea; Gullo, Maria Assunta Lo; Tracanelli, Stefano (Giornale botanico italiano, 1996)
Abstract The annual time course of the water relations of six sclerophylls has been studied with the aim of: a) defining strategies adopted for withstanding summer water stress and b) to check whether their common sclerophyllous habitus could represent a case of convergent evolution devoted to a univocal functional role. In particular, Phillyrea latifolia L. showed to behave like a drought tolerant as indicated by deep summer drop in leaf water potential (?1) to near the full turgor loss point (?lp) and in leaf relative water content (RWC) as caused by xylem cavitation. Prunus laurocerasus L. and Laurus nobilis L. showed to be drought avoiding water spenders in that their ?1 dropped in summer causing prompt recovery in RWC. This was made possible by low cavitation in their twigs. Ilex aquifolium L. was a typical drought avoiding water saver in that both ?1 and RWC remained at very high levels throughout the year. Quercus ilex L. behaved like a drought avoiding water spender which switched to drought tolerance in the warmest period of the year. This was explained by its high vulnerability to cavitation. The extreme heterogeneity of the six species studied suggested that sclerophylly cannot be interpreted as an anatomical feature leading to a specific and unifying functional role, at least as regards drought resistance.
doi: 10.1080/11263509609438352
Keywords: drought tolerance (PG); sclerophylls; water relations